2002
DOI: 10.1089/105072502760043459
|View full text |Cite
|
Sign up to set email alerts
|

Better Yield of 18Fluorodeoxyglucose-Positron Emission Tomography in Patients with Metastatic Differentiated Thyroid Carcinoma during Thyrotropin Stimulation

Abstract: To determine whether (18)fluorodeoxyglucose-positron emission tomography (FDG-PET) for the detection of recurrences or metastases of differentiated thyroid carcinoma should be performed during thyrotropin (TSH) suppression or TSH stimulation, eight patients were studied sequentially. After the second FDG-PET scan, a therapeutic (131)I dose was administered with posttherapy scans obtained 10 days later. Both FDG-PET scans were compared with each other and with the (131)I posttherapy whole body scans by two inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 18 publications
2
28
2
5
Order By: Relevance
“…As a matter of fact, more important than the influence of rhTSH or thyroid hormone withdrawal in 18 F-FDG PET/CT is the presence of high levels of Tg (Tg/ TSH or Tg/LT4 > 10 ng/mL). Over the last years, it has been demonstrated that both strategies, with or without TSH stimulation, do not considerably lead to management changes (12,32). Additional factors than sTg that influence 18 F-FDG PET/CT sensitivity are tumor de-differentiation and larger tumor burden (6), as we have seen in our results.…”
Section: Discussionsupporting
confidence: 58%
“…As a matter of fact, more important than the influence of rhTSH or thyroid hormone withdrawal in 18 F-FDG PET/CT is the presence of high levels of Tg (Tg/ TSH or Tg/LT4 > 10 ng/mL). Over the last years, it has been demonstrated that both strategies, with or without TSH stimulation, do not considerably lead to management changes (12,32). Additional factors than sTg that influence 18 F-FDG PET/CT sensitivity are tumor de-differentiation and larger tumor burden (6), as we have seen in our results.…”
Section: Discussionsupporting
confidence: 58%
“…After reading the full text of 13 potentially relevant publications, six were excluded because they were retrospective studies without controls and did not fulfill the inclusion criteria (7,(15)(16)(17)(18)(19). Seven prospective controlled clinical trials with 168 patients were included (8,9,11,(20)(21)(22)(23) …”
Section: Results Of the Searchmentioning
confidence: 99%
“…In our review, seven prospective controlled clinical trials (8,9,11,(20)(21)(22)(23) involving 168 patients were included. Because of the low incidence, prolonged clinical course, and anticipated formidable sample sizes required for DTC, which has an overall excellent prognosis, it will be difficult to design and conduct a Table 2 Characteristics of the imaging factors and quality of the included studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations